Effect of vision impairment on match-related performance and technical variation in attacking moves in Paralympic judo. (13th August 2021) - Kons, Rafael; Krabben, Kai; Mann, David L.; Detanico, Daniele
ABSTRACT: In Paralympic judo for athletes with vision impairment (VI judo) all eligible athletes (i.e. B1, B2 and B3 classes) compete against each other in the same competition. Evidence suggests that athletes with more impairment may be disadvantaged, but that more sensitive measures of performance are necessary to understand the impact of impairment on performance. The aim of this study was to investigate the relationship between Para sport class and technical variation, time-motion variables, and performance in Paralympic judo. All 175 judo matches from the Rio 2016 Paralympic Games were analysed across 129 competitors (82 male and 47 female). The main results indicated that athletes who demonstrated less technical variation also experienced less competitive success, with the functionally blind athletes (class B1) demonstrating less technical variation than partially sighted (class B2 and B3) athletes (p < 0.05). There was no difference in the time-motion variables between sport classes (p > 0.05). We conclude that measures of technical variation are sensitive to differences in impairment and are suitable for studies that investigate the impairment-performance relationship in VI judo. Results further confirm that some athletes with impairment are disadvantaged under the current rules of VI judo.